2005
DOI: 10.1007/s00586-005-0971-x
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar disk herniation with contralateral symptoms

Abstract: IntroductionDuring the workup of a patient with leg pain, finding a contralateral disk herniation without any significant abnormality on the ipsilateral side on imaging studies is a dilemma for a doctor. He is faced with the problem of deciding whether or not the presenting symptoms are related to the herniated disk. In such a situation, the spinal surgeon fears to offer operation due to the risk of failed back surgery syndrome and he either withholds surgery or chooses to explore both sides of the spinal cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 10 publications
4
38
0
Order By: Relevance
“…Anatomical anomalies of the ipsilateral nerve root with a high or low take-off may be protective against compressive forces. Conversely, anomalies of the contralateral nerve root, such as a conjoint origin or shorter lateral recess course, may render it more susceptible to compressive or tractional forces akin to the aetiology of the cervical C5 nerve root syndrome 2 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomical anomalies of the ipsilateral nerve root with a high or low take-off may be protective against compressive forces. Conversely, anomalies of the contralateral nerve root, such as a conjoint origin or shorter lateral recess course, may render it more susceptible to compressive or tractional forces akin to the aetiology of the cervical C5 nerve root syndrome 2 4…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the severity of his weakness, a decision was made for bilateral decompression and left-sided discectomy. Sucu and Gelal4 and Akdeniz et al 6 have suggested in their case series that discectomy on the side of the disc extrusion would be sufficient for resolution of the contralateral symptomatology, and this will be considered in future practices.…”
Section: Discussionmentioning
confidence: 99%
“…Kornberg et al (13) proposed that inconsistent dural attachments to the posterior longitudinal ligaments holds the lumbar nerve roots at certain levels resulting in a more symptomatic traction of the contralateral nerve root. Sucu et al (10) in his series of 5 patients with paracentral disc herniation, suggested a similar mechanism resulting in compression of the contralateral nerve root against the facet joint. However these mechanisms have not been widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for lumbar disc herniation presenting with contralateral leg symptoms is poorly understood (10,11). Kornberg et al (13) proposed that inconsistent dural attachments to the posterior longitudinal ligaments holds the lumbar nerve roots at certain levels resulting in a more symptomatic traction of the contralateral nerve root.…”
Section: Discussionmentioning
confidence: 99%
“…It creates a difficult therapeutic strategy when a surgical treatment is considered, the question being whether the disc herniation is really the cause of the symptoms. The paper by Sucu and Gelal [26], published in the May issue, raises an interesting discussion. Five patients with disc herniation and controlateral symptoms were operated at the side of the disc herniation without exploring the symptomatic side.…”
Section: Disc Herniationmentioning
confidence: 98%